Detecção de adenovírus humanos em amostras de água superficial e esgoto não tratado oriundas de diversos ecossistemas aquáticos da cidade de Belém-PA - SPADA, Paula Katharine de Pontes (Universidade Federal do Pará, 2015)
The enteric viruses are important agents of waterborne diseases. Among these, the human adenovirus (HAdV) assumed importance because they are a major cause of gastroenteritis in children under five years and by its high resistance to physical and chemical factors in the detriment of other viruses in the environment. Several studies have shown no relationship between the presence of indicator bacteria and viruses. Therefore, several authors have suggested the inclusion of these agents as potential indicators of viral and fecal water contamination. The aim of this study was to detect the presence of HAdV in water samples and untreated sewage originating from many aquatic ecosystems from Belém-PA. Six sampling points were selected, among them an untreated sewage: Esgoto do UNA and five catch basins: Porto do Açaí, Ver-o-Peso, Igarapé Tucunduba, Lago Bolonha and Lago Água Preta. A month collection of two liters of water was realized in each point for 24 consecutive months, from Nov/2008 to Oct/2010, in a total of 144 samples. Sterile distilled water was used as negative control for each point and in all tests. The samples were concentrated by adsorption-elution method and then centrifuged to obtain two ml. The DNA was extracted by the Qiagen commercial kit. Were employed the polymerase chain reaction (PCR) and real-time PCR for molecular detection, with specific primers and probes to amplify a specific hexon gene of 301 and 96 bp, respectively. In order to improve the amplified product for genomic sequencing, some samples positive by PCR were subjected to nested PCR using an additional pair of primers that amplify an internal region of 171 bp. Water and sewage samples were sequenced, analyzed and compared to other obtained from GenBank. The HAdV were detected in 59% (85/144) of samples of surface water and untreated sewage. The positivity obtained by PCR was 22,9% (33/144) and by real-time PCR 58.7% (84/143). The first technique detected the virus only in samples from the Igarapé Tucunduba (62,5%) and Esgoto do UNA (75%) and the second in samples from the six points of collection (variation of 25% to 100%). The agent was detected in all the 24 months of the study, being present in at least two points monthly. The real-time PCR was more sensitive in this study, having found the agent in 36,4% (52/143) of samples not detected by PCR. Of the eight samples genotyped all belong to the species F, four related to serotype 40 and four to 41. Our results confirm the high circulation of these pathogens in surface water and sewage of the city, suggesting the inclusion of HAdVs as good indicators fecal and viral contamination of the water. The study of these viruses in aquatic environments is pioneer in Belém and these results are of relevant importance for public health policies and environmental, serving as a basis for further studies in this area.